Transformation Of Gender Relations In Malay Ethnic Marriages In Tanjung Balai City - Nurainun Sitorus; Rosramadhana Rosramadhana (Jurnal Pendidikan, Sains Sosial, dan Agama, 2021)
This research aim For study gender change in marriage ethnicity Malay in the city Tanjungbalai. This study also describes impact gender change as as a process that influences religion, culture and dynamics social. The method used is study qualitative with approach ethnography, which involves observation participatory, interview in-depth and study documentation. Research results reveal that gender relations in Marriage Malay in the city Tanjung Balai show existence change a role that is traditional nature patriarchal going to gender equality, so that seen Woman start involved in a way active in taking decision, implementation procession customs, as well as room public. In addition, changes it also shows the existence of a negotiation process between mark traditional with demands modernity in life society. Change This impact on change meaning aspect culture that becomes more simple and flexible in implementation, as well as aspects reflected social from method view an increasingly diverse society open in support Woman For appear and play a role in space public